Sistem Presensi Karyawan PT. Tigaraksa Satria Berbasis QR Code - Yana, Yusti; Nugroho, Isworo (LPPM UNIKA Santo Thomas Medan, 2022)
Presence shows the presence of the employee in a company and can be used as one of the points for calculating salaries and meal allowances. The presence system is one of the most important components in an office as an employee attendance recorder. This employee attendance system can later be a proof that the employee is already in the office or company. PT. Tigaraksa Satria which is usually done manually (by means of a signature on the attendance register paper) will be able to cause inefficient data collection and has a weakness that allows fraud in recording employee attendance, the fraud is often called an absentee deposit, therefore a system is needed which can be used to address fraud as well as more specific data collection on employee attendance. QR code has the advantage of being easy to read from various directions, large capacity, small size, can be resistant to dirty and not easily damaged. In this way the QR code can be used as the basis for the development of a presence system. In order to avoid cheating in attending attendance or leaving attendance, employees must take a face photo when making attendance with a QR code. PT. Tigaraksa Satria based on QR code can validate every process on the system such as login, data entry, attendance and so on.